2008
DOI: 10.1016/j.ijid.2008.05.802
|View full text |Cite
|
Sign up to set email alerts
|

T-705, A Novel Anti-Influenza Virus Compound - the Safety, Tolerability and Pharmacokinetics in Human

Abstract: Background: Little is currently known about the immunopathogenesis of dengue virus infection. However, the complex interaction of host immune responses during dengue virus infection has important implications on the clinical outcome of patients. The role of Th genes during dengue virus infection is poorly defined.Methods: In this project, we determine which genes are differentially regulated in dengue type 2 virus-infected cell lines (HepG2 -hepatocytes, K562 -myelogenous leukaemia cell line and Jurkat -T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The longer elimination half-life of the parent drug can be explained by the expected impairment of renal function by the PICV infection. In humans, the principal elimination route of favipiravir is metabolism to M1, which is eliminated in the urine (Kobayashi et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer elimination half-life of the parent drug can be explained by the expected impairment of renal function by the PICV infection. In humans, the principal elimination route of favipiravir is metabolism to M1, which is eliminated in the urine (Kobayashi et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…It is also important to consider the impact of species differences in aldehyde oxidase (Pryde et al, 2010; Ueda et al, 2005), which can have a significant impact on the activity of favipiravir as the primary enzyme catalyzing the conversion of favipiravir to the inactive M1 metabolite (Kobayashi et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Broad-spectrum activity of favipiravir against RNA viruses such as West Nile virus, poliovirus, Ebola virus and norovirus (Rocha-Pereira et al, 2012) makes it a suitable candidate for SARS-CoV-2. Phase I clinical trials to evaluate its efficacy against SARs-CoV-2 have begun and doses ranging from 30 to 1600 mg/kg have shown no serious adverse effects (Kobayashi et al, 2008). Unfortunately, a more recent study (Furuta et al, 2017), has shown that favipiravir has teratogenic and/or embryotoxic effects.…”
Section: Antiviral Drugsmentioning
confidence: 99%